Influence of neck rotation and neck lateroflexion on mandibular equilibrium - Schindler, Hans J.; Lenz, J.; Türp, J. C.; Schweizerhof, K.; Rues, Stefan (Journal of oral rehabilitation, 2010)
Neuromuscular interaction between neck and jaw muscles has been reported in several studies. However, the influence of experimentally modified posture of the neck on jaw muscle activity during isometric biting was not investigated so far. The aim of the present study was to test by the aid of simultaneous electromyographic and intraoral bite force measurements whether neck rotation and lateroflexion, in contrast to a straightforward neck position, change the isometric cocontraction patterns of masticatory muscles under identical submaximum bite forces of 50-200 N. Electric muscle activity of all masticatory muscles and changes of the reduction point (RP) of the resultant bite force vectors were examined. An anteroposterior displacement of the RPs could be observed for the rotated and lateroflexed neck position in comparison with the straightforward position. On the other hand, the results revealed no significant differences between bilateral muscle activation under the different test conditions. These findings suggest a force transmission between the neck and the masticatory system, but no essential activity changes in the masticatory muscles under short time posture modification of the neck.